The Influence of Digital Marketing and Product Quality on Consumer Purchase Interest in the Shopee Marketplace in Biringkanaya District - Rinaya Citra Aulia; Moh Aris Pasigai; Syarthini Indrayani (GoodWill, 2026)
The purpose of this research is to find out the Effect of Digital Marketing and Product Quality on Consumer Buying Interest on Shopee Marketplace. Located on Jl. Sutami Engineer, Biringkanaya District, Untia Village. As many as 50 people. Sample data collection technique using saturated sample technique. The type of data used in this study is quantitative data obtained from the shared questionnaire and related to the problem being studied. Data collection techniques are carried out with questionnaires (sores), observation and documentation. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this research uses the Likert scale method and research data using statistical calculations though the Statistics for the social Science (SPSS) application version 25. Based on research results, it is shown that the digital marketing variable does not have a positive and significant effect on customer purchasing interest as evidenced by the results of the calculated t test = 0.620 > t table 2.012 and the significant value of 0.538 < 0.05. The product quality chart has a positive and significant effect on customer purchasing interest as evidenced by the results of the calculated t test = 0.00 < t table 3.801 and a significant value of 0.00 > 0.05 so that it can be concluded that H1 is accepted H2